Multi-wavelength Brillouin fiber laser using dual-cavity configuration - Parvizi, R.; Ali, N.M.; Harun, Sulaiman Wadi; Moghavvemi, Mahmoud; Arof, Hamzah; Ahmad, Harith (IOP Publishing, 2011)
A simple technique for achieving multi-wavelength tunable multi-wavelength Brillouin fiber laser (BFL) based on dual-pass configuration is demonstrated. The BFL uses a piece of 10 km long non-zero dispersion shifted fiber (NZ-DSF) as a Brillouin gain medium to obtain odd-order Brillouin Stokes waves as an output with the line spacing of 0.16 nm (20 GHz) between each two consecutive waves by employing even-order Brillouin Stokes to improve output performance of the laser. With a BP of 15.3 dBm, at least 15 odd-order Brillouin Stokes and anti-Stokes lines are generated. The laser is room temperature stable, tunable over 50 nm wavelength range and has an optical signal to noise ratio of more than 30 dB at 1560 nm region. This Brillouin fiber laser can operate at any wavelength depending on the Brillouin pump (BP) wavelength used